PEMBELAJARAN PRAKARYA SEBAGAI PROSES BUDAYA DALAM ANTROPOLOGI PENDIDIKAN SEKOLAH DASAR - Putri Zaera, Sonia; Rahmad Syah Putra; Bansu Irianto Ansari; Ummu Kholifatul Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Craft learning in elementary schools is not only oriented toward the development of students’ motor skills and creativity, but also functions as a medium for cultural learning from the perspective of educational anthropology. This article aims to examine craft learning as a cultural process that represents the values, symbols and social practices of local communities within the educational context.This study employs a descriptive qualitative approach through a literature review and analysis of craft learning practices in elementary schools. The findings indicate that craft learning plays a role as a medium for cultural transmission, the strengthening of local identity, and the internalization of social and cultural values among students. Based on these findings, craft learning has a strategic role in integrating education and culture, as well as supporting social transformation in elementary schools.